Coseismic and postseismic slip associated with the 2010 Maule Earthquake, Chile: Characterizing the Arauco Peninsula barrier effect. Issue 6 (17th June 2013) - Lin, Yu‐nung Nina; Sladen, Anthony; Ortega‐Culaciati, Francisco; Simons, Mark; Avouac, Jean‐Philippe; Fielding, Eric J.; Brooks, Benjamin A.; Bevis, Michael; Genrich, Jeff; Rietbrock, Andreas; Vigny, Christophe; Smalley, Robert; et al.
Abstract: [1] Observations of coseismic and postseismic deformation associated with the 2010 Mw = 8.8 Maule earthquake in south‐central Chile provide constraints on the spatial heterogeneities of frictional properties on a major subduction megathrust and how they have influenced the seismic rupture and postseismic effects. We find that the bulk of coseismic slip occurs within a single elongated patch approximately 460 km long and 100 km wide between the depths of 15 and 40 km. We infer three major patches of afterslip: one extends northward along strike and downdip of the major coseismic patch between 40 and 60 km depth; the other two bound the northern and southern ends of the coseismic patch. The southern patch offshore of the Arauco Peninsula is the only place showing resolvable afterslip shallower than 20 km depth. Estimated slip potency associated with postseismic slip in the 1.3 years following the earthquake amounts to 20–30% of that generated coseismically. Our estimates of the megathrust frictional properties show that the Arauco Peninsula area has positive but relatively low ( a − b ) σ n values (0.01 0.22 MPa), that would have allowed dynamic rupture propagation into this rate‐strengthening area and afterslip. Given the only modestly rate‐strengthening megathrust friction in this region, the barrier effect may be attributed to its relatively large size of the rate‐strengthening patch. Coseismic and postseismic uplift of the Arauco Peninsula exceeds interseismic subsidence since the time of the last major earthquake in 1835, suggesting that coseismic and postseismic deformation has resulted in some permanent strain in the forearc. Key Points: The Arauco area is the only place with shallower afterslip The Arauco area owes its barrier effect to its large width Co‐ and post‐seismic effects may be responsible for the uplift of Arauco area